PASAR OPSI SAHAM INDONESIA: AKANKAH KEMBALI AKTIF DAN MENDATANGKAN KEUNTUNGAN BAGI INVESTOR? - , Bagus Panuntun; , Prof. Dr. Jogiyanto Hartono, MBA, Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aimed to investigate whether to conduct a transaction of Stock Option Contracts (KOS) in Indonesia Stock Exchange can still be profitable for investors. In addition, this study also aims to finding the cause that can make the Stock Option Contracts (KOS) instrument become less attractive to investors. To answer these objectives, researchers using the entire transaction data of Stock Option Contracts (KOS) for a period of 2007 & 2008 as the object of research. The study was conducted using secondary data in the archives of Indonesia Stock Exchange, with the underlying assets of PT. Astra International Indonesia, Tbk (ASII), PT. Bank Central Asia Tbk (BBCA), PT. Indofood Sukses Makmur Tbk (INDF) and PT. Telekomunikasi Indonesia, Tbk (TLKM). The sampling technique is using archival data with a purposive sampling method. The results showed that trading Stock Option Contracts (KOS) on the Indonesian Stock Exchange has not been able to bring optimum profit to the investor. With the limitations of published data sources and different trading mechanisms to stock market that has been better known by the investors increase the investorsâ difficulties to get profit in the KOS deal.